Development of PF Resin from Rice Straw Lignin Solid for Plywood Composite - Chawla, Vipin K.; Yadav, Ranjana; Pandey, C. N.; Jain, R. K.; Dixit, A. K. (Indian Forester, 2013)
Lignin-phenol-formaldehyde (LPF) resins were produced by substituting phenol with rice straw lignin in various percentages. Wood adhesive is certainly the most widely explored avenue of lignin utilization. Phenol was replaced by various percentages of lignin to keep the phenolic to formalin weight ratio constant to 1:1.8. 10%, 20% and 30% replacement of phenol by lignin were adopted in making lignin phenol formaldehyde resin (LPF Resin). The plywood panels of 4 mm thick, 30 Ã— 30cm were made and the panels were subjected to test as per IS: 848:2006, specification for synthetic resin adhesives for plywood (Phenolic and Amino plastics). The results indicated that rice straw lignin was a feasible replacement for up to 30% of the phenol in PF resins.